Electrocatalyst and preparation method thereof
By using the composite and surface modification technology of carbon nanoma and polymer materials in the electro -catalyst, the problem of low catalytic efficiency caused by the small number of active sites of the existing electrocatalyst, and achieve higher catalytic efficiency and selectivity.
Patent Information
- Application Number
- CN202310934477.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2025-01-28
AI Technical Summary
The small number of active sites of existing electrocatalysts leads to low catalytic efficiency.
Electric catalysts including carbon nanomaterials and polymer materials, carbon nanomaterials include graphene, carbon nanotubes, charcoal black, etc., polymer materials include polyacryl acid, polyetterol, etc. The ratio is 5: 95-35: 65. Improve the decentralized and active center exposure of carbon nanoma through composite and surface modification.
Improve the catalytic efficiency of the electrocatalyst, especially the selectivity of H2O2 products in the wide potential range, which enhances the activity, selectivity, and stability of the catalyst.
Smart Images

Figure CN119372687A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of catalyst technology, and in particular to an electrocatalyst and a preparation method thereof. Background Art
[0002] In the field of electrocatalytic oxygen reduction to produce H2O2, efficient electrocatalysts are the key factor restricting electrocatalytic oxygen reduction. Electrocatalysts need to have high selectivity, stability and activity to promote the generation of H2O2 through two-electron transfer of oxygen. Currently, the two major types of electrocatalysts used in industry mainly include precious metals and non-precious metal catalysts. However, these two types of electrocatalysts have the problem of low catalytic efficiency due to the small number of active sites. Summary of the invention
[0003] The present application mainly provides an electrocatalyst and a preparation method thereof to solve the problem of low catalytic efficiency caused by a small number of active sites in existing catalysts.
[0004] In order to solve the above technical problems, the first technical solution adopted by the present application is: to provide an electrocatalyst, which includes a carbon nanomaterial and a polymer material. The carbon nanomaterial includes at least one of graphene, carbon nanotubes, carbon black, graphene oxide, oxidized carbon nanotubes, and oxidized carbon black; the polymer material includes at least one of polyacrylic acid, polyethylene glycol, polyvinyl alcohol, polyethylene, polyacrylonitrile, polyacrylamide, polyvinyl chloride, carboxymethyl cellulose, and polyurethane. In the electrocatalyst, the mass ratio of the polymer material to the carbon nanomaterial is 5:95-35:65.
[0005] In some embodiments, the mass ratio of the polymer material to the carbon nanomaterial is 5:95-55:45.
[0006] In some embodiments, the molecular weight of the polymer material is 5,000-25,000.
[0007] In some embodiments, the molecular weight of the polymer material is 5,000-15,000.
[0008] The second technical solution adopted in the present application is to provide a method for preparing an electrocatalyst. The preparation method comprises: preparing a first mixture with a solvent according to a mass ratio of a polymer material to a carbon nanomaterial of 5:95-35:65, wherein the carbon nanomaterial comprises at least one of graphene, carbon nanotubes, carbon black, graphene oxide, oxidized carbon nanotubes, and oxidized carbon black, and the polymer material comprises at least one of polyacrylic acid, polyethylene glycol, polyvinyl alcohol, polyethylene, polyacrylonitrile, polyacrylamide, polyvinyl chloride, carboxymethyl cellulose, and polyurethane; washing the first mixture to obtain a second mixture; and drying the second mixture to obtain the electrocatalyst as described above.
[0009] In some embodiments, the steps of configuring a first mixture with a solvent according to a mass ratio of a polymer material to a carbon nanomaterial of 5:95-35:65 include: preparing a polymer dispersion; preparing a carbon nanomaterial dispersion; mixing the polymer dispersion and the carbon nanomaterial dispersion to obtain a first mixture, in which the mass ratio of the polymer material to the carbon nanomaterial is 5:95-35:65.
[0010] In some embodiments, the polymer material is mixed with a first solvent to form a polymer material dispersion, and the first solvent includes one or a mixture of methanol, ethanol, ethylene glycol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide carbon tetrachloride, ethylene glycol, acetonitrile, and N-methylpyrrolidone.
[0011] In some embodiments, in the polymer material dispersion, the concentration of the polymer material is 0.5-35 mg / mL.
[0012] In some embodiments, the step of preparing a carbon nanomaterial dispersion includes: mixing the carbon nanomaterial with a second solvent to form a carbon nanomaterial dispersion, wherein the second solvent includes one or a mixture of methanol, ethanol, ethylene glycol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide carbon tetrachloride, ethylene glycol, acetonitrile, and N-methylpyrrolidone.
[0013] In some embodiments, in the carbon nanomaterial dispersion, the concentration of the carbon nanomaterial is 10-120 mg / mL.
[0014] The beneficial effects of the present application are as follows: Different from the prior art, the present application discloses an electrocatalyst and a preparation method thereof. The electrocatalyst includes a carbon nanomaterial and a polymer material, the carbon nanomaterial includes at least one of graphene, carbon nanotubes, carbon black, graphene oxide, oxidized carbon nanotubes, and oxidized carbon black, and the polymer material includes at least one of polyacrylic acid, polyethylene glycol, polyvinyl alcohol, polyethylene, polyacrylonitrile, polyacrylamide, polyvinyl chloride, carboxymethyl cellulose, and polyurethane. In the electrocatalyst, the mass ratio of the polymer material to the carbon nanomaterial is 5:95-35:6. The polymer material and the carbon nanomaterial are compounded to improve the dispersibility of the carbon nanomaterial while modifying the surface of the carbon nanomaterial, exposing more catalytic active centers, and thus improving the catalytic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0016] Figure 1 is an electron microscope image of the electrocatalyst provided in Example 1 of the present application;
[0017] Figure 2 This is the method for preparing the electrocatalyst provided in the embodiments of the present application;
[0018] Figure 3 yes Figure 2 Some steps of the method for preparing an electrocatalyst;
[0019] Figure 4 The performance test curve of the electrocatalyst prepared in Examples 1 and 2 and Comparative Example 1 of the present application is obtained when the catalyst loading on the glassy carbon disk electrode is 0.5 mg / cm 2 The following is obtained by linear scanning curve test;
[0020] Figure 5 The electrochemical performance test curve of the electrocatalyst prepared in Example 1 of the present application is shown in Figure 1. The catalyst loading on the glassy carbon rotating disk ring electrode is 0.5 mg / cm 2 The following is obtained by linear scanning curve test;
[0021] Figure 6 The electrochemical performance test curve of the electrocatalyst prepared in Example 2 of the present application is obtained when the catalyst loading on the glassy carbon rotating disk ring electrode is 0.5 mg / cm 2 The following is obtained by linear scanning curve test;
[0022] Figure 7 The electrochemical performance test curve of the electrocatalyst prepared in Comparative Example 1 of the present application is obtained. The curve is obtained when the catalyst loading on the glassy carbon rotating disk ring electrode is 0.5 mg / cm 2 The following is obtained by linear scanning curve test. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0024] The terms "first", "second", "third" in the embodiments of the present application are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. Thus, the features defined as "first", "second", "third" can expressly or implicitly include at least one of the features. In the description of the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device comprising a series of steps or units is not limited to the listed steps or units, but optionally also includes steps or units that are not listed, or optionally also includes other steps or units inherent to these processes, methods, products or devices.
[0025] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0026] In the related art, how to achieve two-electron reduction to generate hydrogen peroxide under different potential conditions while electrocatalyzing oxygen reduction and suppress the competitive reaction of four-electron transfer is of great significance for the efficient preparation of hydrogen peroxide. Although progress has been made in the preparation of hydrogen peroxide by electrocatalytic oxygen reduction, the electrocatalytic preparation of hydrogen peroxide still faces the following major problems in terms of catalysts: (1) High catalyst cost. Catalysts are expensive, and the precious metal properties of elements such as palladium and gold limit their large-scale application. (2) Complex catalyst preparation process. Non-precious metal catalysts, such as single-atom catalysts, generally require high-temperature pyrolysis methods. The complexity of the process preparation of such electrocatalysts limits their large-scale application. (3) Narrow catalytic potential application range. The selectivity of the preparation of hydrogen peroxide by precious metals and transition metal oxides is low in a wide potential range, which limits the development of in-situ preparation of hydrogen peroxide. (4) Small number of active sites. There are few active center sites in the catalyst, and the difficulty in improving them leads to low catalytic efficiency.
[0027] In view of this, the present application provides an electrocatalyst. Figure 1 As shown, Figure 1It is an electron microscope image of the electrocatalyst provided in Example 1 of the present application. The electrocatalyst includes a carbon nanomaterial and a polymer material. The carbon nanomaterial includes at least one of graphene, carbon nanotubes, carbon black, graphene oxide, oxidized carbon nanotubes, and oxidized carbon black; the polymer material includes at least one of polyacrylic acid, polyethylene glycol, polyvinyl alcohol, polyethylene, polyacrylonitrile, polyacrylamide, polyvinyl chloride, carboxymethyl cellulose, and polyurethane. Among them, in the electrocatalyst, the mass ratio of the polymer material to the carbon nanomaterial is 5:95-35:65.
[0028] Carbon nanomaterials refer to carbon materials with at least one dimension of the dispersed phase smaller than 100nm. The dispersed phase can be composed of carbon atoms, heterogeneous atoms (non-carbon atoms), or even nanopores. The chemical properties of graphene are similar to those of graphite. Graphene can adsorb and desorb various atoms and molecules. When these atoms or molecules act as donors or acceptors, they can change the concentration of graphene carriers, while graphene itself can maintain good conductivity. Carbon nanotubes are seamless, hollow tubes formed by graphene sheets formed by carbon atoms. They can generally be divided into single-walled carbon nanotubes, multi-walled carbon nanotubes, and double-walled carbon nanotubes. The main component of carbon black is elemental carbon, and it contains a small amount of oxygen, hydrogen, sulfur, etc. Carbon black particles are approximately spherical, and many carbon black particles often fuse or aggregate into three-dimensional bonded dendrites or fibrous aggregates. Graphene oxide is a layered material after graphene is oxidized, characterized by rich surface functional groups and high catalytic activity. Oxidized carbon nanotubes are a material obtained by oxidizing carbon nanotubes. Oxidized carbon black is a material obtained by oxidizing carbon black. In electrocatalysts, carbon nanomaterials act as catalysts and provide active centers.
[0029] In some embodiments, the electrocatalyst may include a mixture of graphene and polyacrylic acid, a mixture of carbon nanotubes and polyvinyl alcohol, a mixture of graphene oxide and polyacrylonitrile, a mixture of carbon black and polyurethane, or a mixture of oxidized carbon nanotubes and carboxymethyl cellulose, etc. In other embodiments, the electrocatalyst may also include: a mixture of graphene, carbon nanotubes and polyvinyl alcohol; a mixture of carbon black, graphene oxide, oxidized carbon nanotubes and polyethylene glycol; a mixture of carbon nanotubes, polyvinyl alcohol and polyethylene; a mixture of graphene, oxidized carbon black and polyacrylic acid, etc.
[0030] In some embodiments, the mass ratio of the polymer material to the carbon nanomaterial can be 5:95, 15:85, 20:80, 24:76, 28:72, 30:70, 32:68, 35:65, etc., or a range consisting of any two of the above values, for example, it can be 5:95-24:76, 15:85-24:76, 15:85-30:70, 30:70-35:65, etc. In the electrocatalyst, the carbon nanomaterial acts as a catalyst and provides an active center, and the polymer material plays a role in modifying the surface of the carbon nanomaterial, thereby making the electrocatalyst have a higher H2O2 product selectivity, especially in a wide potential range. When the mass ratio of the polymer material to the carbon nanomaterial is lower than 5:95, the mass ratio of the polymer material is small, and the surface modification of the polymer material cannot be fully exerted; when the mass ratio of the polymer material to the carbon nanomaterial is higher than 35:65, the mass ratio of the carbon nanomaterial is small, and the role of the active center of the carbon nanomaterial cannot be fully exerted. Therefore, the mass ratio of the polymer material to the carbon nanomaterial is limited to the above range, so that the carbon nanomaterial in the electrocatalyst can provide sufficient active centers after surface modification, thereby fully exerting the role of the electrocatalyst.
[0031] The electrocatalyst provided in the embodiment of the present application includes carbon nanomaterials and polymer materials, the carbon nanomaterials include at least one of graphene, carbon nanotubes, carbon black, graphene oxide, oxidized carbon nanotubes, and oxidized carbon black, the polymer materials include at least one of polyacrylic acid, polyethylene glycol, polyvinyl alcohol, polyethylene, polyacrylonitrile, polyacrylamide, polyvinyl chloride, carboxymethyl cellulose, and polyurethane, and in the electrocatalyst, the mass ratio of the polymer material to the carbon nanomaterial is 5:95-35:6. The polymer material and the carbon nanomaterial are compounded, and the dispersibility of the carbon nanomaterial is improved while the surface of the carbon nanomaterial is modified, and more catalytic active centers are exposed, so that the activity, selectivity, and stability of the electrocatalyst can be regulated, especially in a wide potential range, with a high selectivity for H2O2 products, thereby improving the catalytic efficiency.
[0032] In some embodiments, the mass ratio of the polymer material to the carbon nanomaterial is 5:95-30:70. For example, it can be 5:95, 12:88, 22:82, 24:76, 28:72, 30:70, etc., or a range consisting of any two of the above values, for example, it can be 5:95-12:88, 12:88-22:82, 22:82-30:70, etc. The mass ratio of the polymer material to the carbon nanomaterial is further limited within the above range, so that the carbon nanomaterial in the electrocatalyst is surface-modified to provide sufficient active centers, thereby giving full play to the role of the electrocatalyst.
[0033] In some embodiments, the molecular weight of the polymer material is 5000-25000. For example, in some embodiments, the polymer material can be polyacrylic acid, polyethylene glycol, polyvinyl alcohol, polyethylene, polyacrylamide, carboxymethyl cellulose or polyurethane, etc. In some embodiments, the polymer material can also be a mixture of polyacrylic acid and polyethylene glycol, a mixture of polyethylene and carboxymethyl cellulose, etc. The molecular weight of any of the above polymer materials may be 5000, 6000, 7000, 8000, 9000, 9500, 11000, 13150, 15000, 16500, 17000, 20000, 22000, 23500, 25000, etc., or a range consisting of any two of the above values, for example, 5000-6000, 7000-8000, 9000-9500, 11000-13150, 15000-16500, 17000-20000, 20000-23500, 23500-25000, etc. When the molecular weight of the polymer material is lower than 5000 or higher than 25000, the surface modification effect of the polymer material is not good. By controlling the molecular weight of the polymer material within the above range, the surface modification effect of the polymer material on the carbon nanomaterial can be enhanced.
[0034] In some embodiments, the molecular weight of the polymer material is 5000-15000. By further controlling the molecular weight of the polymer material within the above range, the surface modification effect of the polymer material on the carbon nanomaterial can be enhanced.
[0035] like Figure 2 As shown, the following embodiment of the present application provides a method for preparing an electrocatalyst. The preparation method includes the following steps.
[0036] S10: preparing a first mixture with a solvent according to a mass ratio of the polymer material to the carbon nanomaterial of 5:95-35:65.
[0037] Among them, the carbon nanomaterial includes at least one of graphene, carbon nanotubes, carbon black, graphene oxide, oxidized carbon nanotubes, and oxidized carbon black, and the polymer material includes at least one of polyacrylic acid, polyethylene glycol, polyvinyl alcohol, polyethylene, polyacrylonitrile, polyacrylamide, polyvinyl chloride, carboxymethyl cellulose, and polyurethane. For example, in some embodiments, the polymer material can be polyethylene glycol, polyvinyl alcohol, or polyethylene. In some embodiments, the polymer material can also be a mixture of polyvinyl alcohol and polyacrylamide, a mixture of polyacrylic acid and carboxymethyl cellulose, etc. The above polymer materials are low in cost and can all be obtained through commercial channels.
[0038] like Figure 3As shown, in some embodiments, S10: preparing a first mixture with a solvent according to a mass ratio of polymer material to carbon nanomaterial of 5:95-35:65.
[0039] In some embodiments, step S10 may include the following steps:
[0040] S101: preparing a polymer material dispersion.
[0041] In some embodiments, the step of preparing a polymer material dispersion may specifically include: mixing the polymer material with a first solvent to form a polymer material dispersion. The first solvent includes one or a mixture of methanol, ethanol, ethylene glycol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide carbon tetrachloride, ethylene glycol, acetonitrile, and N-methylpyrrolidone. For example, in some embodiments, polyvinyl alcohol can be slowly added dropwise to ethanol to obtain a polyvinyl alcohol dispersion. Slow addition results in a good dispersion effect.
[0042] In some embodiments, in the polymer material dispersion, the concentration of the polymer material is 0.5-35 mg / mL. For example, the concentration of the polymer material can be 0.5 mg / mL, 2.6 mg / mL, 4.7 mg / mL, 6.5 mg / mL, 8 mg / mL, 10.5 mg / mL, 14 mg / mL, 16 mg / mL, 18.5 mg / mL, 21 mg / mL, 24 mg / mL, 27.6 mg / mL, 29.4 mg / mL, 30 mg / mL, 32 mg / mL, 35 mg / mL, etc., or a range consisting of any two of the above values, such as 0.5-4.7 mg / mL, 4.7-6.5 mg / mL, 6.5-10.5 mg / mL, 10.5-16 mg / mL, 16-21 mg / mL, 21-27.6 mg / mL, 29.4-30 mg / mL, 32-35 mg / mL, etc. When the concentration of the polymer material is lower than the above range, that is, the polymer material is too little, it is not conducive to the surface modification effect of the carbon nanomaterial after the subsequent composite with the carbon nanomaterial; when the concentration of the polymer material is higher than the above range, it is not conducive to the full dispersion of the polymer material. By limiting the concentration of the polymer material to the above range, the dispersibility of the polymer material and the surface modification effect of the carbon nanomaterial after the composite with the carbon nanomaterial can be taken into account, so that the catalytic effect is good.
[0043] S102: preparing a carbon nanomaterial dispersion.
[0044] In some embodiments, the specific steps of preparing the carbon nanomaterial dispersion may include: mixing the carbon nanomaterial with a second solvent to form a carbon nanomaterial dispersion. The second solvent includes methanol, ethanol, ethylene glycol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide carbon tetrachloride, ethylene glycol, acetonitrile, N-methylpyrrolidone, or a mixture thereof. For example, carbon nanotubes are dispersed in an ethanol solution to obtain a carbon nanotube dispersion.
[0045] In some embodiments, in the carbon nanomaterial dispersion, the concentration of the carbon nanomaterial is 10-120 mg / mL. For example, the concentration of the carbon nanomaterial can be 10 mg / mL, 14 mg / mL, 25 mg / mL, 30 mg / mL, 43 mg / mL, 54 mg / mL, 66 mg / mL, 75 mg / mL, 82 mg / mL, 97 mg / mL, 105 mg / mL, 112 mg / mL, 120 mg / mL, etc., or a range consisting of any two of the above values, such as 10-14 mg / mL, 14 -25 mg / mL, 25-54 mg / mL, 43-66 mg / mL, 54-82 mg / mL, 75-97 mg / mL, 97-105 mg / mL, 105-120 mg / mL, etc. If the concentration of the carbon nanomaterial is lower than the above range, that is, the carbon nanomaterial is too little, resulting in a small number of active sites of the carbon nanomaterial; if the concentration of the carbon nanomaterial dispersion is higher than the above range, it is not conducive to the full dispersion of the carbon nanomaterial. By limiting the concentration of the carbon nanomaterial to the above range, the number of active sites of the carbon nanomaterial and the dispersibility of the carbon nanomaterial can be taken into account, so that the catalytic effect is good.
[0046] It is noted that in some embodiments, the order of step S101 and step S102 can be interchanged, that is, the carbon nanomaterial dispersion can be prepared first, and then the polymer material dispersion can be prepared. Separately preparing the carbon nanomaterial dispersion and the polymer material dispersion can improve the dispersibility of the carbon nanomaterial and the polymer material and reduce excessive aggregation of the carbon nanomaterial and the polymer material.
[0047] S103: Mixing the polymer material dispersion and the carbon nanomaterial dispersion to obtain a first mixture, wherein the mass ratio of the polymer material to the carbon nanomaterial is 5:95-35:65.
[0048] In some embodiments, the stirring time for mixing the polymer material dispersion and the carbon nanomaterial dispersion is 2-15 hours, and the stirring temperature is 25-75°C. For example, the stirring time for the polymer material dispersion and the carbon nanomaterial dispersion can be 2h, 4h, 5.5h, 7h, 8.5h, 9.5h, 11h, 13h, 14h, 15h, etc. For example, the stirring temperature for the polymer material dispersion and the carbon nanomaterial dispersion can be 25°C, 35°C, 46°C, 50°C, 55°C, 60°C, 66°C, 70°C, 72°C, 75°C, etc. Limiting the stirring time and stirring temperature of the polymer material dispersion and the carbon nanomaterial dispersion to the above range can fully mix the polymer material and the carbon nanomaterial to obtain a well-dispersed first mixture.
[0049] In some embodiments, the mass ratio of the polymer material to the carbon nanomaterial can be 5:95, 15:85, 20:80, 24:76, 28:72, 30:70, 32:68, 35:65, etc., or a range consisting of any two of the above values, for example, it can be 5:95-15:85, 15:85-24:76, 24:76-30:70, 30:70-35:65, etc. In the electrocatalyst, the carbon nanomaterial acts as a catalyst and provides an active center, and the polymer material plays a role in modifying the surface of the carbon nanomaterial, thereby making the electrocatalyst have a higher H2O2 product selectivity, especially in a wide potential range. When the mass ratio of the polymer material to the carbon nanomaterial is lower than 5:95, the mass ratio of the polymer material is small, and the surface modification of the polymer material cannot be fully exerted; when the mass ratio of the polymer material to the carbon nanomaterial is higher than 35:65, the mass ratio of the carbon nanomaterial is small, and the role of the active center of the carbon nanomaterial cannot be fully exerted. Therefore, the mass ratio of the polymer material to the carbon nanomaterial is limited to the above range, so that the carbon nanomaterial in the electrocatalyst can provide sufficient active centers after surface modification, thereby fully exerting the role of the electrocatalyst.
[0050] It should be noted that the solvent in step S10 is a mixture of the first solvent and the second solvent.
[0051] In addition, in some embodiments, step S10 may also be: mixing the polymer material and the carbon nanomaterial in a mass ratio of 5:95-35:65 to obtain a mixture, and then dispersing the mixture of the polymer material and the carbon nanomaterial in a solvent.
[0052] In some embodiments, step S10 may also be: first dispersing one of the polymer material and the carbon nanomaterial in a solvent, and then dispersing the other in a solvent, according to a mass ratio of the polymer material to the carbon nanomaterial of 5:95-35:65.
[0053] S20: washing the first mixture to obtain a second mixture.
[0054] For example, the solvent used to wash the first mixture includes ethanol and / or deionized water. For example, the first mixture can be washed 3 times with ethanol and 3 times with deionized water to fully remove impurities such as the first solvent and the second solvent.
[0055] S30: Drying the second mixture to obtain the electrocatalyst as described above.
[0056] In some embodiments, the drying time of the second mixture is greater than or equal to 24 hours. For example, the drying time of the second mixture can be 24 hours, 25 hours, 26 hours, 28 hours, 30 hours, 32 hours, etc. The drying time is limited to the above range so that the second mixture can be fully dried.
[0057] The polymer materials and carbon nanomaterials required for the preparation method of the electrocatalyst are widely available and of low cost. In addition, the preparation method of the electrocatalyst has a simple process, a fast reaction speed, and low requirements for mass production equipment of the materials, which can effectively reduce production costs.
[0058] The beneficial effects of the present application are further illustrated below in conjunction with embodiments.
[0059] In order to make the technical problems, technical solutions and beneficial effects solved by the embodiments of the present application clearer, the following will be further described in detail with reference to the embodiments and the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0060] 1. Preparation of electrocatalysts
[0061] Example 1
[0062] Carbon nanotubes and polyvinyl alcohol were weighed according to a mass ratio of 80:20, and dispersed in ethanol under ultrasound to obtain a nanotube dispersion, which was added to the polyvinyl alcohol dispersion. The carbon nanotube dispersion was added to the polyvinyl alcohol dispersion, and ultrasound was continued for 2 hours under ultrasound. The mixed solution was magnetically stirred at room temperature for 6 hours to obtain a first mixture. The obtained first mixture was centrifuged at high speed, and washed and centrifuged with ethanol and water for 3 times to obtain a second mixture. The obtained second mixture was placed in a vacuum drying oven and dried for 26 hours, and the obtained solid powder was the electrocatalyst.
[0063] The difference between Examples 2-15 and Comparative Example 1 and Example 1 is that the raw material formula and / or the parameters of the preparation method are different, as shown in Table 1 for details.
[0064] 2. Performance Test
[0065] 1. Current density
[0066] The catalyst loading on the glassy carbon disk electrode was 0.5 mg / cm 2 The following is obtained by linear scanning curve test.
[0067] 2. Hydrogen peroxide yield at a voltage of 0.5 V
[0068] The catalyst loading on the glassy carbon disk electrode was 0.5 mg / cm 2 The following is obtained by linear scanning curve test.
[0069] 3. Number of electron transfers
[0070] The catalyst loading on the glassy carbon disk electrode was 0.5 mg / cm 2 The following is obtained by linear scanning curve test.
[0071]
[0072] Please refer to Table 1 and combine Figure 4 , Figure 5 , Figure 6 and Figure 7 .in, Figure 4 The performance test curve (the relationship between the test voltage and the current density) of the electrocatalyst prepared in Examples 1 and 2 and Comparative Example 1 of the present application is obtained. The curve is obtained when the catalyst loading on the glassy carbon disk electrode is 0.5 mg / cm 2 The following is obtained by linear scanning curve test; Figure 5 The electrochemical performance test curve (hydrogen peroxide yield and electron transfer number curve) of the electrocatalyst prepared in Example 1 of the present application is obtained when the catalyst loading on the glassy carbon rotating disk ring electrode is 0.5 mg / cm 2 The following is obtained by linear scanning curve test; Figure 6 The electrochemical performance test curve (hydrogen peroxide yield and electron transfer number curve) of the electrocatalyst prepared in Example 2 of the present application is obtained when the catalyst loading on the glassy carbon rotating disk ring electrode is 0.5 mg / cm 2 The following is obtained by linear scanning curve test; Figure 7 The electrochemical performance test curve (hydrogen peroxide yield and electron transfer number curve) of the electrocatalyst prepared in Comparative Example 1 of the present application is obtained when the catalyst loading on the glassy carbon rotating disk ring electrode is 0.5 mg / cm 2The following is obtained by linear scanning curve test.
[0073] Compared with Examples 1-15 and Comparative Example 1, the electrocatalysts in Examples 1-15 include carbon nanomaterials and polymer materials, and the mass ratio of polymer materials to carbon nanomaterials is 5:95-35:65. The electrocatalysts provided in the present application have a high hydrogen peroxide yield, that is, the electrocatalysts provided in the present application have a good catalytic effect.
[0074] Compared with Examples 11 and 15, the molecular weight of the polymer material included in the electrocatalysts of Examples 1 and 12-14 is 5000-25000, the molecular weight of the polymer material included in the electrocatalysts of Examples 11 and 15 is not within the range defined in the present application, and the hydrogen peroxide in Examples 1 and 12-14 is higher than that in Examples 11 and 15. Therefore, when the molecular weight of the polymer material included in the electrocatalyst is 5000-25000, the catalytic effect of the electrocatalyst is good.
[0075] Furthermore, compared with Examples 11 and 15, the hydrogen peroxide in Examples 1-10 and 12-14 is higher than that in Examples 11 and 15. Therefore, when the molecular weight of the polymer material included in the electrocatalyst is 5000-25000, the catalytic effect of the electrocatalyst is good.
[0076] In summary, the present application discloses an electrocatalyst and a preparation method thereof. The electrocatalyst includes a carbon nanomaterial and a polymer material, the carbon nanomaterial includes at least one of graphene, carbon nanotubes, carbon black, graphene oxide, oxidized carbon nanotubes, and oxidized carbon black, and the polymer material includes at least one of polyacrylic acid, polyethylene glycol, polyvinyl alcohol, polyethylene, polyacrylonitrile, polyacrylamide, polyvinyl chloride, carboxymethyl cellulose, and polyurethane. In the electrocatalyst, the mass ratio of the polymer material to the carbon nanomaterial is 5:95-35:6. The polymer material and the carbon nanomaterial are compounded to improve the dispersibility of the carbon nanomaterial while modifying the surface of the carbon nanomaterial, exposing more catalytic active centers, and thus improving the catalytic efficiency.
[0077] The above descriptions are merely embodiments of the present application and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. An electrocatalyst, characterized in that Including carbon nanomaterials and polymer materials; The carbon nanomaterial includes at least one of graphene, carbon nanotubes, carbon black, graphene oxide, oxidized carbon nanotubes, and oxidized carbon black; The polymer material includes at least one of polyacrylic acid, polyethylene glycol, polyvinyl alcohol, polyethylene, polyacrylonitrile, polyacrylamide, polyvinyl chloride, carboxymethyl cellulose and polyurethane; Wherein, in the electrocatalyst, the mass ratio of the polymer material to the carbon nanomaterial is 5:95-35:
65.
2. The electrocatalyst according to claim 1, characterized in that The mass ratio of the polymer material to the carbon nanomaterial is 5:95-30:
70.
3. The electrocatalyst according to claim 1, characterized in that The molecular weight of the polymer material is 5000-25000.
4. The electrocatalyst according to claim 3, characterized in that The molecular weight of the polymer material is 5000-15000.
5. A method for preparing an electrocatalyst, characterized in that: The preparation method comprises: A first mixture is prepared with a solvent according to a mass ratio of the polymer material to the carbon nanomaterial of 5:95-35:65, wherein the carbon nanomaterial comprises at least one of graphene, carbon nanotubes, carbon black, graphene oxide, oxidized carbon nanotubes, and oxidized carbon black, and the polymer material comprises at least one of polyacrylic acid, polyethylene glycol, polyvinyl alcohol, polyethylene, polyacrylonitrile, polyacrylamide, polyvinyl chloride, carboxymethyl cellulose, and polyurethane; washing the first mixture to obtain a second mixture; The second mixture is dried to obtain the electrocatalyst as claimed in claim 1 or 2.
6. The method for preparing an electrocatalyst according to claim 5, characterized in that: The step of preparing the first mixture with the solvent according to the mass ratio of the polymer material to the carbon nanomaterial of 5:95-35:65 comprises: Preparing polymer material dispersion; preparing a carbon nanomaterial dispersion; The polymer material dispersion and the carbon nanomaterial dispersion are mixed to obtain the first mixture, wherein the mass ratio of the polymer material to the carbon nanomaterial is 5:95-35:
65.
7. The method for preparing an electrocatalyst according to claim 6, characterized in that: The step of preparing the polymer material dispersion comprises: The polymer material is mixed with a first solvent to form the polymer material dispersion, wherein the first solvent includes one or a mixture of methanol, ethanol, ethylene glycol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide carbon tetrachloride, ethylene glycol, acetonitrile, and N-methylpyrrolidone.
8. The method for preparing an electrocatalyst according to claim 6 or 7, characterized in that: In the polymer material dispersion, the concentration of the polymer material is 0.5-35 mg / mL.
9. The method for preparing an electrocatalyst according to claim 8, characterized in that: The step of preparing the carbon nanomaterial dispersion comprises: The carbon nanomaterial is mixed with a second solvent to form the carbon nanomaterial dispersion, wherein the second solvent comprises one or a mixture of methanol, ethanol, ethylene glycol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide carbon tetrachloride, ethylene glycol, acetonitrile, and N-methylpyrrolidone.
10. The method for preparing an electrocatalyst according to claim 6 or 9, characterized in that: In the carbon nanomaterial dispersion, the concentration of the carbon nanomaterial is 10-120 mg / mL.